Reducing a possibility of transport congestion on freeways using ramp control management - Lagerev, Roman; Kapski, Denis; Burinskienė, Marija; Barauskas, Andrius (Transport, 2017)
Merge junctions are the key elements in the freeway system, as they are likely to function as bottlenecks. Investigations into breakdown occurrence at ramp junctions have demonstrated that when the groups of several vehicles following each other enter the freeway from the ramp, they are expected to create ‘turbulence’ resulting from lane changes, decelerations of vehicles on the mainline and inevitably by the cars merging from the on-ramp. This turbulence can lead to breakdown when the level of mainline demand is adequately high. In other words, the impact of a ramp vehicle on capacity is higher than that of a mainline vehicle, which indicates that a part of vehicles will simultaneously occupy two lanes during the process of changing them thus momentarily decreasing the capacity of the link. This feature becomes particularly important near bottlenecks where it might reduce the already limited throughput. The article introduces the main approaches, methodology, principles and stages of transport demand management on freeways that are aimed at improving the operation quality of transport facilities, including road safety. The technique allows evaluating and optimizing a Ramp-Metering (RM) concept from the viewpoint of minimizing the length of queues on ramps and a possibility of transport congestion. The proposed algorithm estimates the probability of starting congestion formation on the ramp using objective information on traffic conditions in each segment of the highway, which is based on the criterion for vehicle density on the lane. The last chapter shows the examples of traffic flow optimization on Western bypass ramps in Vilnius comparing two strategies for access control management using one or several vehicles per lane. Conclusions, trends and work on future investigations are presented at the end of the article.